(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the role and significance of the information-analytical approach in the process of forming media culture among students. It also explores the pedagogical foundations for the development of media literacy, information culture, and critical thinking competencies in the educational process within the context of the digital era.